(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
In the article new approaches over of perfection of algorithm of treatment ЭКГ are brought for the increase of authenticity of determination of macronutrients in blood. Treatment of these EKG is in-process examined by means of method of decomposition on the empiric fashions of Huang, that allows to analyses and process the nonlinear and non-stationary systems. His distinguishing feature consists of that, that the base functions of decomposition are determined adaptive on the basis of the processed data. Also in this article approaches over of renewal of standard trajectories EKG are brought by means of the signal shaping in a complex plane, that promotes quality of output and treatment of electrocardiograms considerably. It is offered authors in future, for the estimation of standard fragment of EKG to use the methods of processing of images, in particular to apply the contour concerted filtration.